A pilot study to assess radiographer preliminary clinical evaluation (PCE) introduced for emergency department adult appendicular X-ray examinations: Comparison of trained and untrained radiographers. Issue 2 (March 2023) - Lidgett, T.; Pittock, L.; Piper, K.; Woznitza, N.
Abstract: Introduction: Radiographers are transitioning from using "Red Dot" annotations to flag abnormal emergency X-ray images, to providing written preliminary clinical evaluation (PCE) diagnostic comments. This study explored the impact of local training on radiographers' PCE participation and accuracy performance during a trial period. Methods: Ten radiographers provided PCE comments for adult appendicular trauma X-ray examinations performed in the Emergency Department of an English public hospital over a 19 week trial period. Five senior radiographers who had received local PCE training and five more recently qualified radiographers, without this local training, participated in the trial. PCE participation rates were recorded and the PCE comments were scored for accuracy compared to the formal radiology report. Results: There were 796 eligible examinations, of which 528 (66%) had PCE comments. PCE participation was significantly higher (p < 0.001) for the radiographer group who received the training (80%, 253/316) compared to the untrained group (57%, 275/480). Similar levels of PCE accuracy (90% vs. 89%), sensitivity (86% vs. 82%) and specificity (91% vs. 93%) were found for the trained and untrained cohorts respectively, with no statistically significance difference between these scores. Conclusion: Local PCE training was associated with more frequent PCE participation but did not appear to influence PCE accuracy. The accuracy results suggest that radiographers are well equipped to provide PCE comments for adult appendicular X-ray examinations. Implications for practice: Local PCE training is likely to be important for consistent PCE scheme participation. Both experienced and recently qualified radiographers appear well equipped to provide accurate PCE for adult appendicular trauma X-ray examinations.